The Skandapurāṇa III Adhyayas 34.1-61, 53-69: The Vindhyavāsinī Cycle - Yokochi, Yuko (Groningen Oriental Studies, Supplement, 2013)
Skandapurāṇa III presents a critical edition of the Vindhyavāsinī Cycle (Adhyāyas 34.1-61, 53-69) from the Skandapurāṇa , with an introduction and annotated English synopsis.The work is currently only available in print as an exact reprint done in a smaller book size (15.5 x 23.5 cm) than the first printrun.; Readership: All interested in Purana literature, early Saivism, Hindu mythology, Hinduism in general, and especially the history of goddess worship; and also some interested in editing the Sanskrit literature.